VALIDITAS DAN EFEKTIVITAS LEMBAR KERJA SISWA BERBASIS CONTEXTUAL TEACHING AND LEARNING MATERI CERMIN UNTUK KELAS VIII SMP TAHUN 2018 - rinda wahyuningtyas; Nur Kuswanti; Lina Arifah Fitriyah (Jurnal Pembelajaran Sains, 2019)
This research was a development research that aim to produce teaching materials in the form of Student Worksheets based un Contextual Teaching and Learning on Mirror material.  This study used ADDIE development model, with stages of Analysis, Design, Development, Implementation, and Evaluation. This study used instruments in the form of worksheets validation sheets, worksheets material validation sheets, and posttest sheets. The result of the study showed that the worksheets developed had met the aspects of validity, and effectiveness. The validity aspect was shown by the results of the worksheets validation of 3,71 and the results of the worksheets material validation of 3,92 with very valid categories. The mastery of student learning outcomes amounted to be 77,8 (Effective), and mastery of learning objective was 78,8 including the effective category. So that it can be concluded that the worksheets developed were qualified and worthy of being used as a learning resource.